Identification of bacteriophage T4 prereplicative proteins on two-dimensional polyacrylamide gels. - Kutter, E M (1994)
Bacteriophage T4 makes a large number of prereplicative proteins, which are involved in directing the transition from host to phage functions, in producing the new T4 DNA, and in regulating transcriptional shifts. We have used two-dimensional gel electrophoresis (nonequilibrium pH gradient electrophoresis gels in the first dimension and sodium dodecyl sulfate-polyacrylamide gradient slab gels in the second) to identify a number of new prereplicative proteins. The products of many known genes are identified because they are missing in mutants with amber mutations of those genes, as analyzed by us and/or by previous workers. Some have also been identified by running purified proteins as markers on gels with labeled extracts from infected cells. Other proteins that are otherwise unknown are characterized as missing in infections with phage carrying certain large deletions and, in some cases, are correlated with sequence data.